Non-exchanging hydroxyl groups on the surface of cellulose fibrils: The role of interaction with water. (3rd November 2016) - Lindh, Erik L.; Bergenstråhle-Wohlert, Malin; Terenzi, Camilla; Salmén, Lennart; Furó, István
Abstract: The interaction of water with cellulose stages many unresolved questions. Here 2 H MAS NMR and IR spectra recorded under carefully selected conditions in 1 H- 2 H exchanged, and re-exchanged, cellulose samples are presented. It is shown here, by a quantitative and robust approach, that only two of the three available hydroxyl groups on the surface of cellulose fibrils are exchanging their hydrogen with the surrounding water molecules. This finding is additionally verified and explained by MD simulations which demonstrate that the 1 HO(2) and 1 HO(6) hydroxyl groups of the constituting glucose units act as hydrogen-bond donors to water, while the 1 HO(3) groups behave exclusively as hydrogen-bond acceptors from water and donate hydrogen to their intra-chain neighbors O(5). We conclude that such a behavior makes the latter hydroxyl group unreactive to hydrogen exchange with water. Graphical abstract: Highlights: Cellulose-water interaction was examined by 2 H MAS NMR and FTIR using hydrogen-deuterium exchange. Only two of the three available hydroxyl groups on cellulose are exchanging their hydrogen. MD simulations confirm that only the HO(2) and HO(6) hydroxyl groups act as hydrogen bond donors.